Multi-objective grey wolf optimization of solar chimneys based on an improved model incorporating a wind turbine power curve. (1st July 2021) - Habibollahzade, Ali; Fakhari, Iman; Mohsenian, Saeed; Aberoumand, Hossein; Taylor, Robert A.
Highlights: A modified model is presented for solar chimneys considering power curve of turbine. Performance of the system was assessed through steady-state and transient simulations. Establishing taller towers and bigger collectors cannot necessarily improve performance. When airspeed inside the tower exceeds 15 m/s, the modified model is more accurate. Optimum annual power and levelized cost of electricity are 121.4 GWh and 0.28 $/kWh. Abstract: In this study, a modified theoretical model is presented, which incorporates the wind turbine power curve as an important limiting factor to avoid overestimating the power generation of solar chimneys. Steady-state and annual performance simulations were performed for a full year based on hourly resolution using meteorological variables of Western Australia (Exmouth, near Perth), Japan (Nagoya), and UAE (Dubai) as characteristic places with abundant, scarce, and medium solar radiation intensity, respectively. A parametric study was also conducted to assess the effect of tower and collector radius and tower height on the power output and the levelized cost of electricity, LCOE . Finally, the solar chimney was optimized through multi-objective grey wolf optimization—a fast and robust technique—to balance the annual power generation and LCOE objective functions. The results showed that, contrary to the reported results in the literature, increasing the tower height and collector radius is not always beneficial, and extreme values can negatively affect the performance of the system. Further, the outcomes showed that higher values for tower radius could increase annual power generation while reducing LCOE . The multi-objective optimization results revealed that tower heights of more than 400 m, a collector radius between 2200 m and 3200 m, and a tower radius of 120 m represent the most suitable range of design parameters for the locations studied. Using the optimum designs, the annual power output and LCOE for Australia, Japan, and UAE were determined to be 121.4 GWh and 0.28 $/kWh, 113.0 GWh and 0.43 $/kWh, and 111.9 GWh and 0.32 $/kWh, respectively. Overall, very large solar chimneys with a tower height and collector radius greater than 500 m and 1000 m were shown not to provide better LCOE . However, optimally designed solar chimneys do provide attractive power generation profiles and costs, especially in locations with abundant solar radiation.